2013
DOI: 10.1371/journal.pone.0071743
|View full text |Cite|
|
Sign up to set email alerts
|

Human Hemorrhagic Pulmonary Leptospirosis: Pathological Findings and Pathophysiological Correlations

Abstract: BackgroundLeptospirosis is a re-emerging zoonosis with protean clinical manifestations. Recently, the importance of pulmonary hemorrhage as a lethal complication of this disease has been recognized. In the present study, five human necropsies of leptospirosis (Weil‘s syndrome) with extensive pulmonary manifestations were analysed, and the antibodies expressed in blood vessels and cells involved in ion and water transport were used, seeking to better understand the pathophysiology of the lung injury associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 30 publications
2
29
0
1
Order By: Relevance
“…However, studies with double-knockout mice for AQP1 and 5 revealed that the absence of these channels did not alter alveolar fluid clearance [5, 24], suggesting that aquaporins add little fluid clearance management if active salt transport is intact. Nevertheless, subsequent studies showed that the expression of lung AQPs are altered after ALI models [1012, 25, 26]. Although marginally significant, our results showed that the AQP1 level was lower in the DAD group as reported in previous animal models.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…However, studies with double-knockout mice for AQP1 and 5 revealed that the absence of these channels did not alter alveolar fluid clearance [5, 24], suggesting that aquaporins add little fluid clearance management if active salt transport is intact. Nevertheless, subsequent studies showed that the expression of lung AQPs are altered after ALI models [1012, 25, 26]. Although marginally significant, our results showed that the AQP1 level was lower in the DAD group as reported in previous animal models.…”
Section: Discussionsupporting
confidence: 52%
“…We also found the increased expression of AQP5 in the DAD groups. The role of AQP5 in edema reabsorption in ALI models is controversial [1012, 25, 26]. The AQP5 response to lung injury may fluctuate over time and is dependent on the intensity and type of injury [11, 12, 26].…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Also, experimental and autopsy studies have shown endothelial necrosis and capillary thrombosis in lung tissue. 13,14 Another important component of the endothelium is the glycocalyx, a 1-μm carbohydrate-rich structure located at the top of the endothelium. It has antiadhesive and anticoagulant properties that protect the endothelium and maintain the vascular barrier function.…”
Section: Introductionmentioning
confidence: 99%
“…It may lead to a severe multiorgan failure (Morbus Weil, or Weil's disease) (7). In recent years, life-threatening and fatal cases have been due most often to pulmonary hemorrhages caused by vasculitis of small vessels (1,6,(8)(9)(10).…”
mentioning
confidence: 99%